2016
DOI: 10.1097/igc.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNA-21 Is Involved in Lymph Node Metastasis in Cervical Cancer by Targeting RASA1

Abstract: The aims of this study were to discover if increased circulating microRNA-21 (miR-21) expression in serum is associated with lymph node metastasis in patients with cervical cancer and look further into the molecular mechanism of these. Whole-blood samples from 89 patients who have been histopathologically confirmed as having cervical cancer and 20 control subjects were collected, and then the association between lymph node metastasis and the level of circulating miR-21 was compared. Then cervical cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 17 publications
3
41
0
1
Order By: Relevance
“…RASA1 is ubiquitously expressed across different tissue types. Although previous studies revealed that RASA1 may play tumor suppressive roles in many cancer types (12,14,15), the correlation between the role of RASA1 expression, tumor differentiation and overall survival in HCC have not been previously addressed in detail. This study shows that RASA1 protein is rarely expressed in HCC, especially in poor differentiated and undifferentiated tumors or large-sized tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RASA1 is ubiquitously expressed across different tissue types. Although previous studies revealed that RASA1 may play tumor suppressive roles in many cancer types (12,14,15), the correlation between the role of RASA1 expression, tumor differentiation and overall survival in HCC have not been previously addressed in detail. This study shows that RASA1 protein is rarely expressed in HCC, especially in poor differentiated and undifferentiated tumors or large-sized tumors.…”
Section: Discussionmentioning
confidence: 99%
“…RASA1 has been involved in many biological processes including actin filament polymerization, cellular apoptosis, and cell migration (13). Besides, several studies indicated that onco-microRNAs (micorRNA-21 and micorRNA-182) can promote tumor angiogenesis or lymph node metastasis by targeting RASA1 (14,15). Therefore, RASA1 functions as a tumor suppressor in several types of cancer.…”
mentioning
confidence: 99%
“…Ten of 15 included studies had selected circulating HPV DNA as a detected gene target. Other gene targets had higher sensitivity but lower specificity, including SIM1 methylation [26], MEG3 methylation [28], Bmi-1 [29], miR-21 [30], and hsa-miR-92a [31].…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) was mainly applied to detect ctDNA in the studies included in this analysis. Two studies [10,27] used Taqman PCR, and another three studies [29][30][31] used reverse transcription PCR. Additionally, two studies [17,32] used droplet digital PCR (ddPCR), and three studies [24,26,28] used methylation-specific (MSP) PCR.…”
Section: Detection Of Ctdna and Target Genesmentioning
confidence: 99%
See 1 more Smart Citation